Islamic ethics and commitment among Muslim nurses in Indonesia - Ramadhan, Muhammad; Alazzawi, Fouad Jameel Ibrahim; Islam, Md. Zahidul; Kosasih, Kosasih; Chupradit, Supat; K, Nurdin; Sunarsi, Denok; Alshahrani, Najim Z.; Iswanto, A. Heri (AOSIS (Pty) Ltd, 2022)
Ethical principles are among the topics that are widely emphasised in the Islamic society. Ethics is a set of values, do’s and don’ts that can play an important role in the effective management of organisations. If employees of organisations, especially medical staff, are working in the atmosphere of Islamic ethics, they show functional behaviours in line with the goals and missions of organisation. Due to the direct relationship and treatment of nurses with recipients of medical services, nurses’ behaviours have significant impact on the quality of services provided by medical centres. Therefore, the purpose of this study is to explore the relationship between Islamic ethics and commitment of 1100 Muslim nurses in Indonesia in 2021. This study was performed by descriptive-analytical correlational method. Data were collected using Islamic ethics and organisational commitment questionnaires and measured by Pearson correlation coefficient in Statistical Package for the Social Sciences (SPSS) and structural equation modelling analysis (SEM) in linear structural relationships (LISREL). The results indicate that Islamic ethics have significant and positive relationship with nurses’ commitment as p = 0.542 and t = 5.63. Contribution: According to the research findings, it can be concluded that commitment of nurses can be improved by applying Islamic ethics in medical centres.